1977
DOI: 10.1093/cvr/11.2.94
|View full text |Cite
|
Sign up to set email alerts
|

Creatine kinase isoenzymes: their separation and quantitation

Abstract: The cardiospecificity of the MB isoenzyme of creatine kinase, EC 2.7.3.2, (CK) with its associated diagnostic and research value has resulted in the development of a number of procedures for the separation and quantitation of the three isoenzymes of CK. In our experience methods involving cellulose acetate electrophoresis, apposition incubation, and fluoroscanning for quantitation are of limited linearity, insensitive, and irreproducible. We have, therefore, developed a method which overcomes these difficultie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
1

Year Published

1977
1977
1997
1997

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 0 publications
0
12
1
1
Order By: Relevance
“…It is known from the literature that in the heart muscle 30-41% of the total creatine kinase activity occurs äs MB isoenzyme in humans* 28 ± 2% in rats, 13 ± 4% in dogs and 4% in pigs (2,8,9,10). A rise in MB isoenzyme activity in the serum has been reported in rats after isoproterenöl-indüced cardiac damage (1), in dogs after occlusion of the left anterior descending coronary artery (9) and in rabbits in blood samples obtained after cardiac puncture (4).…”
Section: Resultsmentioning
confidence: 99%
“…It is known from the literature that in the heart muscle 30-41% of the total creatine kinase activity occurs äs MB isoenzyme in humans* 28 ± 2% in rats, 13 ± 4% in dogs and 4% in pigs (2,8,9,10). A rise in MB isoenzyme activity in the serum has been reported in rats after isoproterenöl-indüced cardiac damage (1), in dogs after occlusion of the left anterior descending coronary artery (9) and in rabbits in blood samples obtained after cardiac puncture (4).…”
Section: Resultsmentioning
confidence: 99%
“…But, as Schon and co-workers (Shanske et al, 1987;Sakoda et al, 1988) have indicated, a lack of detection of M-PGM transcript does not exclude low transcription of M-PGM message in the brain. Most authors have reported that BB-CK is the only CK cytosolic isoenzyme present in human brain based upon electrophoretic (Deul and Van Breemen, 1964;Sjovall and Voigt, 1964;Dawson and Fine, 1967;Kumudavalli and Watts, 1968;Allard and Cabrol, 1970;Smith, 1972;Klein et al, 1973;Ogunro et al, 1977;Petronia et al, 1980;Urdal et al, 1983;Chandler et al, 1984;Chastain et al, 1988), chromatographic (Roberts et al, 1975;Tsung, 1976) and immunological techniques (Jockers-Wretou and Pfleiderer, 1975;Wevers et al, 1981;Chandler et al, 1984;Chastain et al, 1988). However, some authors have reported the presence of MM-CK.…”
Section: Discussionmentioning
confidence: 99%
“…Samples with activity more than 250 mU/ml were diluted before determination of total CK; in order to minimise the dilutionactivation effect observed with plasma CK, heat inactivated plasma was used as the diluent (Graig et al, 1967). Isoenzymes were separated by electrophoresis on agarose gel and quantified in aqueous solution by fluorimetry (Ogunro et al, 1977). MB CK isoenzyme release curves were constructed by measuring the plasma MB CK activity (mU/ml) at the stated time intervals after the onset of chest pain.…”
Section: Methodsmentioning
confidence: 99%